Mesenchymal stem cells: A new therapeutic tool for chronic kidney disease - Wang, Jiali; Lin, Yongda; Chen, Xiutian; Liu, Yiping; Zhou, Tianbiao (Frontiers in Cell and Developmental Biology, 2022)
Chronic kidney disease (CKD) has a major impact on public health, which could progress to end-stage kidney disease (ESRD) and consume many medical resources. Currently, the treatment for CKD has many flaws, so more effective treatment tools are urgently required for CKD. Mesenchymal stem cells (MSCs) are primitive cells with self-renewal and proliferation capacity and differentiation potential. Extensive preclinical and clinical data has shown that cell-based therapies using MSCs can modulate immunity, inhibit inflammatory factors, and improve renal function in CKD, suggesting that MSCs have the potential to be a new, effective therapeutic tool for CKD. In this review, we will describe different kinds of MSCs and MSCs products for the treatment of CKD in experimental models and clinical trials, potential signaling pathways, therapeutic efficacy, and critical issues that need to be addressed before therapeutic application in humans.